2016
DOI: 10.1586/14737167.2016.1140574
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness model for the use of a cannabis-derived oromucosal spray for the treatment of spasticity in multiple sclerosis

Abstract: The THC/CBD spray was found to be cost-effective for the treatment of spasticity in MS, and dominant, if home carer costs were included. Use of THC/CBD has the potential to generate cost savings by significantly improving the symptoms of moderate to severe MS spasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Social costs: productivity losses and informal care Productivity losses: human capital approach (early retirement, temporary disability and absenteeism) Informal care: opportunity-cost method (paid and unpaid time) Furneri (2019) [ 37 ] Relapsing–remitting multiple sclerosis Pharmaceutical (disease-modifying therapy: infused medication) Italy (2015€) 3.5%; 3.5% 50 years Societal perspective (healthcare provider’s perspective could be extracted from the tables) Healthcare costs: cost of disability, treatment acquisition, administration, monitoring, relapses, adverse events-related costs Social costs: productivity losses Productivity losses: human capital approach Gani (2008) [ 38 ] Relapsing–remitting multiple sclerosis Pharmaceutical (disease-modifying therapy: infused medication) United Kingdom (2006£) 3.5%; 3.5% 30 years Societal perspective (healthcare provider’s perspective in the sensitivity analysis) Healthcare costs: inpatient admissions, nursing home care, day admissions, rehabilitation, healthcare specialists, diagnostic tests, non-DMT drug costs, home visits by nurses. Social costs: productivity losses Productivity losses: n.a Gras (2016) [ 39 ] Multiple sclerosis Pharmaceutical (cannabis-derived spray) United Kingdom (2014£) 3.5%; 3.5% 30 years Healthcare provider’s perspective (societal perspective in a secondary analysis) Healthcare costs: community-based visits, outpatient clinic visits, A&E visits, hospital admission, home care visits, equipment costs. Social costs: informal care Informal care: n.a Hettle (2018) [ 40 ] Relapsing–remitting multiple sclerosis Pharmaceutical (disease-modifying therapy: oral + infused medications) United Kingdom (2016£) 3.5%; 3.5% 50 years Healthcare provider’s perspective (societal perspective in a secondary analysis) Healthcare costs: drug acquisition, drug administratio...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Social costs: productivity losses and informal care Productivity losses: human capital approach (early retirement, temporary disability and absenteeism) Informal care: opportunity-cost method (paid and unpaid time) Furneri (2019) [ 37 ] Relapsing–remitting multiple sclerosis Pharmaceutical (disease-modifying therapy: infused medication) Italy (2015€) 3.5%; 3.5% 50 years Societal perspective (healthcare provider’s perspective could be extracted from the tables) Healthcare costs: cost of disability, treatment acquisition, administration, monitoring, relapses, adverse events-related costs Social costs: productivity losses Productivity losses: human capital approach Gani (2008) [ 38 ] Relapsing–remitting multiple sclerosis Pharmaceutical (disease-modifying therapy: infused medication) United Kingdom (2006£) 3.5%; 3.5% 30 years Societal perspective (healthcare provider’s perspective in the sensitivity analysis) Healthcare costs: inpatient admissions, nursing home care, day admissions, rehabilitation, healthcare specialists, diagnostic tests, non-DMT drug costs, home visits by nurses. Social costs: productivity losses Productivity losses: n.a Gras (2016) [ 39 ] Multiple sclerosis Pharmaceutical (cannabis-derived spray) United Kingdom (2014£) 3.5%; 3.5% 30 years Healthcare provider’s perspective (societal perspective in a secondary analysis) Healthcare costs: community-based visits, outpatient clinic visits, A&E visits, hospital admission, home care visits, equipment costs. Social costs: informal care Informal care: n.a Hettle (2018) [ 40 ] Relapsing–remitting multiple sclerosis Pharmaceutical (disease-modifying therapy: oral + infused medications) United Kingdom (2016£) 3.5%; 3.5% 50 years Healthcare provider’s perspective (societal perspective in a secondary analysis) Healthcare costs: drug acquisition, drug administratio...…”
Section: Resultsmentioning
confidence: 99%
“…However, the authors considered different time horizons, discount rates, healthcare costs and cost-effectiveness thresholds, which may also limit the comparability of results. Moreover, the stage of the disease might be a relevant factor behind the economic burden of the condition, but there is no consistency in relation to this question, since 10 studies did not specify the degree of severity [33,36,39,42,44,48,[51][52][53][54]57], while 11 studies referred to relapsing-remitting MS individually [31,34,35,37,38,40,41,43,50,55,56] and the other 8 studies considered slow or secondary-progressive MS, solely or jointly with relapsing-remitting MS. Lastly, the search strategy in relation to the databases used might be subject to debate. However, we complemented our search launched in Medline by additionally using the CEA Registry of Tufts University, which applies an algorithm also launched in Medline and a systematic review process [27,78].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of the cost and benefits of cannabisbased medicines for the management of MS reported that Sativex was a cost-effective option in four of the five studies retrieved. These studies were based on decision analytical model simulations and were conducted using healthcare setting from Spain [32], Germany [32], Italy [33], Wales [34], and UK [35] healthcare settings. In the studies where Sativex resulted in cost effectiveness, the ICERs reported were €4968 (Italy), £10,891 (Wales), and €11,214 (Germany) per QALY gained and dominant (less expensive and more effective) in the Spanish analysis.…”
Section: Discussionmentioning
confidence: 99%